Algoritme Genetik untuk Optimasi Pembentukan Fungsi Regresi Linier dalam Menentukan Kebutuhan Volume Air Penyiraman Tanah - Hendra Pratama Budianto; Budi Darma Setiawan; Putra Pandu Adikara (Fakultas Ilmu Komputer (FILKOM), Universitas Brawijaya, 2017)
Seed Laboratory BPTP East Java is one of provincial government work units that have assignment as the technical implementer to conduct a study in seed growth. Currently at this place is being developed automatic watering device based on soil humidity sensor, but the device cannot predict the volume of water needed in order to keep the moist of seed growth media. With the help of humidity sensor on device and expert's knowledge, the observations dataset of soil moisture to the needs of waters volume has been obtained. This study was conducted to apply linear regression method so that the device can perform predictions based on dataset patterns as an equation. The accuracy of prediction results with this method is measured by the coefficient of determination. The coefficient of determination can be decreasing due to the arising of observation outliers because Inaccuracy of observation results. The solution from this study is using genetic algorithm with information criteria as comparison for detecting observation outliers to eliminated. After eliminating 6 observations outliers were detected by genetic algorithms in this study, shows increase in the coefficient of determination from 0.9673 to 0.9935.